A Study of IFN-α-Induced Chemokines CCL2, CXCL10 and CCL19 in Patients with Systemic Lupus Erythematosu - Mariela Gencheva Geneva-Popova; Stanislava Dimitrova Popova-Belova; Petya Nikolova Gardzheva; Krasimir Iliev Kraev (Life, 2022)
The role of IFN-α-induced chemokines CCL2, CXCL10 and CCL19 in different forms of SLE has not been studied in Bulgaria, with worldwide sources attributing varying degrees of importance. The aim of this study was to investigate the correlation between IFN-induced chemokines CCL2, CXCL10 and CCL19 and disease activity in patients with SLE over 24 months. Materials and methods: This study used data from 70 patients with SLE (age range 24–62 years) and a control group of 30 healthy volunteers matched for age and gender. Levels of chemokines CCL2, CXCL10 and CCL19 in lupus patients’ serum were measured by ELISA. The study examined clinical and clinical laboratory indicators, as well as measures of disease activity developed for lupus patients (SLEDAI and SLICC). Statistical program SPSS, Version 26 were used for statistical data processing with p < 0.05. At 24 months of follow-up, 12 patients were with deterioration, and they had an IFN-a of 363.76 ± 9.23 versus 116.1 ± 22.1 pg/mL of those who did not worsen, CCL2 278.3 ± 5.12 versus 89.4 ± 12.8, CXCL10 234.2 ± 6.13 versus 115.23 ± 5.9 p CCL19 776.25 ± 5.1 vs. 651.34 ± 9.0 during the first visit. Results: The mean values of CCL2, CXCL10 and CCL19 were higher in patients with SLE compared to healthy controls (p = 0.01). A strong significant association (p = 0.01) was found between the concentration of CCL2, CXCL10 and CCL19 and with patients’ age, disease duration, SLEDAI and SLICC. Conclusion: CCL2, CXCL10 and CCL19 serum levels were found to correlate with patients’ age and disease duration. The level of IFN-induced chemokines CCL2, CXCL10 and CCL19 has a prognostic value in terms of SLE disease activity and degree of organ damage.